Crossing on time : steam engines, fast ships, and a journey to the New World - Macaulay, David (Roaring Brook Press, 2019)
A picture book discussing the design and construction of the steamboat SS "United States" and the life of its designer and engineer, William Francis Gibbs. Also describes how the author's family emigrated to America on the "United States" when he was ten years old. Includes a timeline, along with blueprints, diagrams, and detailed color illustrations.